Vascular Surprises in Calot’s Triangle during Laproscopic Choleystectomy - Tariq Nawaz, Maryam Barkat, Muhammad Atif, Qasim Ali (Journal of Rawalpindi Medical College, 2017)
Background: To identify the vascular anomalies,variations of Calot’s triangle during laparoscopic cholecystectomy Methods: In this prospective observational study one thousand patients with a diagnosis of cholithiasis were included. Exclusion criteria were patients younger than 12 years and older than 80 year. Calot’s triangle dissection was done meticulously.Cystic artery and hepatic artery anomalies and variations were observed and analyzed on SPSS 21. Results: The age varied from 12 to 80 years. On the basis of distributional variation the cystic artery was single in 90% cases, branched in 7% cases and absent in 3% cases. On positional variations the cystic artery was superomedial to the cystic duct in 85% cases, anterior in 7% cases, and posterior in 3% cases and low lying in 5% of the cases. On the basis of length variation results showed that 80% cases had a normal cystic artery .A short cystic artery was found in 5% cases and a long cystic artery was present in 5%. Other arterial variations are of hepatic artery i.eMoynihan’s Hump (3%) and right hepatic artery present in Calots triangle in 5% Conclusions: For the safety of laparoscopic cholecystectomy one should be well aware of the anatomical variations of the cystic and hepatic artery